Open-source tools for behavioral video analysis: Setup, methods, and best practices - Luxem, Kevin; Sun, Jennifer J; Bradley, Sean P; Krishnan, Keerthi; Yttri, Eric; Zimmermann, Jan; Pereira, Talmo D; Laubach, Mark (eLife, 2023)
Recently developed methods for video analysis, especially models for pose estimation and behavior classification, are transforming behavioral quantification to be more precise, scalable, and reproducible in fields such as neuroscience and ethology. These tools overcome long-standing limitations of manual scoring of video frames and traditional ‘center of mass’ tracking algorithms to enable video analysis at scale. The expansion of open-source tools for video acquisition and analysis has led to new experimental approaches to understand behavior. Here, we review currently available open-source tools for video analysis and discuss how to set up these methods for labs new to video recording. We also discuss best practices for developing and using video analysis methods, including community-wide standards and critical needs for the open sharing of datasets and code, more widespread comparisons of video analysis methods, and better documentation for these methods especially for new users. We encourage broader adoption and continued development of these tools, which have tremendous potential for accelerating scientific progress in understanding the brain and behavior.
Keywords: video; pose estimation; methods; open source; behavior; reproducibility